2006
DOI: 10.1186/1471-2407-6-140
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 expression in urothelial carcinoma: prognostic significance and association with p53 alterations, tumour angiogenesis and extracellular matrix components

Abstract: Background: Thrombospondin-1 (TSP-1) is an extracellular matrix component glycoprotein, which is known to be a potent inhibitor of angiogenesis and may be important in cancer invasiveness. We examined the TSP-1 expression in correlation with conventional clinicopathological parameters to clarify its prognostic significance in bladder cancer. In addition, the possible correlation of TSP-1 expression with microvessel count, VEGF expression, p53 expression as well as with the expression of the extracellular matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 48 publications
7
54
1
2
Order By: Relevance
“…Some researches in their studies found that TSP-1 was distributed in the cytoplasm of tumor cells in thyroid cancer [31], breast cancer [32], hepatocellular carcinoma [33], gastric carcinoma [34], and CRC [19]; while others studies showed that TSP-1 was mainly expressed in the ECM in pancreatic cancer [35], CRC [16], esophageal squamous cell carcinoma [36], non-small cell lung cancer [10], ductal in situ carcinoma of the breast [37]. However, others studies reported TSP-1 expression in both cytoplasm and stroma, as well in CRC [9], bladder cancer [13], and breast cancer [38]. Thus, the expression mode of TSP-1 in tumors could vary in different tissues or organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researches in their studies found that TSP-1 was distributed in the cytoplasm of tumor cells in thyroid cancer [31], breast cancer [32], hepatocellular carcinoma [33], gastric carcinoma [34], and CRC [19]; while others studies showed that TSP-1 was mainly expressed in the ECM in pancreatic cancer [35], CRC [16], esophageal squamous cell carcinoma [36], non-small cell lung cancer [10], ductal in situ carcinoma of the breast [37]. However, others studies reported TSP-1 expression in both cytoplasm and stroma, as well in CRC [9], bladder cancer [13], and breast cancer [38]. Thus, the expression mode of TSP-1 in tumors could vary in different tissues or organs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relationship between the expression of TSP-1 and wild-type p53, in the manner that loss of wild-type p53 being associated with loss of TSP-1 expression [8,9]. Decreased expression of the TSP-1 is correlated with metastatic potential in prostate cancer [10], non-small lung cancer [11], breast cancer [12], and bladder cancer [13]. In CRC, TSP-1 has been shown to have both an angiogenic effect [14,15] and conversely be associated with venous invasion and tumour progression [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, other investigators showed the expression of DPD, TP or OPRT to be correlated with various clinicopathological factors, prognosis and efficacy of 5-FU agents (14,(25)(26)(27)(28). Although the reason for these discrepancies was unclear, trials to verify prognosis and efficacy of the 5-FU agents while taking clinicopathological factors into account are a crucial strategic objective to further validate useful biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23,27] Thrombospondin-1 is expressed in the stroma and cancer cells. [70] TNC, a key metastatic niche molecule required for the metastasis initiation, is also expressed in breast tumor cells and stroma cells. [8,16,18] Collagens are mainly synthesized by cancer-associated fibroblasts in breast cancer, but cancer cells are also an important source of the collagen.…”
Section: Cancer Cells Are Critical Sources Of Tumor Ecmmentioning
confidence: 99%